Participation and losses in multi‐level marketing: Evidence from a Federal Trade Commission settlement. Issue 1 (10th March 2022) - Bäckman, Claes; Hanspal, Tobin
Abstract: More than 20 million Americans are affiliated with multi‐level marketing firms (MLMs), but there is little empirical evidence on who participates in this controversial part of today's labor market. We link data on 350, 000 individuals cited in an Federal Trade Commission settlement with one of the largest MLMs to detailed county‐level information. We find that the share of refund claimants is greater in areas with higher median income and where women are absent from the labor market, suggesting value in flexible work. However, check amount, a proxy for losses, are correlated with higher inequality and lower social capital, suggesting that the pitfalls accrue to vulnerable groups.